IMPLEMENTATION OF ISLAMIC EDUCATION POLICY IN MUSLIM MINORITY COUNTRIES (Case Study of Islamic Education in Thailand) - Rohimah; Kurniawan, Imam; Maryani, Novi; Suherman, Irman; Nurhaidah, Siti Nuri (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This study aims to analyze Islamic education policies in Muslim minority countries (Thailand). The research method used is a case study. Data was collected through interviews and documentation and then analyzed using NVivo 12. The results of this study illustrate that there are three primary forms of Islamic Education policy models in Muslim minority countries (Thailand), namely (1) laws or government regulations, (2) Islamic Education Curriculum, and (3) Provision of Islamic Education budget. This model of Islamic Education policy shows that the Thai government pays attention to the Muslim population, even though they are a minority population. There was turmoil in the Muslim region of Thailand, so the government made laws or regulations, created an Islamic education curriculum, and created a budget for the development of Islamic education. So that there is a change in culture and language, open accessibility of Islamic education, and support for the implementation of worship in the Thai Muslim community.